Kriptografi Menggunakan Hybrid Cryptosystem dan Digital Signature - Halim Agung (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2016)
Security of information at this point becomes easier to be abused by another party when that information is sent and stored. To overcome these problems then do research to create an application that uses a hybrid method cryptosystem and digital signature. Methods in hybrid cryptosystem is done by combining the RC4 and RSA. Digital signature method is done by using a hash function SHA-512 with RSA algorithm approach. Applications that are built to perform encryption and decryption on files as well as improving security in sending data by hybrid cryptosystem and digital signature. Based on the research results of all the file types tested successfully encrypted and decrypted as well as the larger the file size, the longer the encryption and decryption process.